2018
DOI: 10.17659/01.2018.0039
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Cannulation of Left Superior Intercostal Vein: A Rare Instance of Central Venous Catheter Malpositioning

Abstract: Background: Central venous catheter (CVC) placement plays an important role in the management of critically ill patients. Complication rates have been reduced with the use of image guidance for their placement. Sometimes, particularly in emergency situation or due to lack of image guidance accidental malpositioning of these catheters can occur further adding to morbidity of the critically ill patients. Case Report: Herein we report a case of CVC placement into left superior intercostal vein during a left sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As mentioned in the introduction, the course of central venous catheterization procedures may be complicated by unintentional insertion (or spontaneous displacement) of a CVC into the left SICV or the left IMV [3,8,11,20]. The venography records from CIED implantations analyzed in this study showed two cases of the left IMVs, one of which resulted in an unintentional lead insertion (as described in the text above).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…As mentioned in the introduction, the course of central venous catheterization procedures may be complicated by unintentional insertion (or spontaneous displacement) of a CVC into the left SICV or the left IMV [3,8,11,20]. The venography records from CIED implantations analyzed in this study showed two cases of the left IMVs, one of which resulted in an unintentional lead insertion (as described in the text above).…”
Section: Resultsmentioning
confidence: 81%
“…Unintentional CVC insertion into a wrong vessel, particularly as the catheter is being introduced via the left jugular or left subclavian vein, typically involves the left superior intercostal vein (SICV) or the left internal thoracic (mammary) vein (IMV) [5][6][7][8][9][10].…”
mentioning
confidence: 99%